National wastewater reconnaissance of artificial sweetener consumption and emission in Australia. (October 2020) - Li, Dandan; O'Brien, Jake W.; Tscharke, Benjamin J.; Choi, Phil M.; Zheng, Qiuda; Ahmed, Fahad; Thompson, Jack; Li, Jiaying; Mueller, Jochen F.; Sun, Hongwen; Thomas, Kevin V.
Graphical abstract: Highlights: Direct injection LC-MS/MS method to simultaneously quantify seven artificial sweeteners in wastewater. Cyclamate, aspartame, acesulfame, sucralose and saccharin were detected in 90% of Australian wastewater influent samples. Summed artificial sweetener influent loads were between 2.5 and 50 mg person −1 day −1 . National daily artificial sweetener consumption was estimated to be 1004 kg. 14% of the artificial sweeteners consumed in Australia are released into the environment. Abstract: Artificial sweeteners are used as sugar substitutes in our daily lives yet consumption and release patterns are currently unknown in Australia. The spatial distribution of artificial sweetener consumption and WWTP effluent emission in Australia was estimated by wastewater analysis. Wastewater influent and effluent samples were collected from 69 WWTPs across Australia during the week of the 2016 Australian census. Mean population-weighted per capita loads for individual artificial sweeteners (cyclamate, aspartame, acesulfame, sucralose, saccharin) ranged from 0.12 ± 0.14 mg d −1 p −1 for aspartame to 6.9 ± 2.8 mg d −1 p −1 for acesulfame with 1004 kg of these artificial sweeteners being consumed daily in Australia. Significant removal of aspartame (100%), cyclamate (92 ± 18%) and saccharin (88 ± 21%) was observed during wastewater treatment. The average per capita release to the environment for individual artificial sweeteners (cyclamate, acesulfame, sucralose, saccharin) ranged from 230 ± 780 mg d −1 1000p −1 (cyclamate) to 3800 ± 1400 mg d −1 1000p −1 (sucralose). The daily release of artificial sweeteners from Australian WWTPs was estimated to be 142 kg suggesting that 14% of the artificial sweeteners consumed in Australia are released into the environment. To the best of our knowledge, this is the first wastewater study to estimate the occurrence and population-normalized artificial sweetener consumption and emission in Australia.